Toward Integral Holism in Psychology - Vadakkemuriyil, A. (Journal of Dharma, 1990)
Being a fruitful outcome of a serious research into the holistic and reductionistic tendencies in modern psychology. This work of Bastin J. Parangimalil is a remarkable contribution to the scholars of psychology and other related fields. The book contains 8 chapters including the foreword by Dr. J. Harold Ellens. The first chapter studies the general division of holism in psychology namely preventive, discriptive, and integral, tracing their origin to the corresponding philosophical disciplines like Aristotelian, Thomistic and the Neo-Scholastic trends. The second chapter is a brief but comprehensive discussion on the various reductionist philosophical disciplines which influenced the reductionistic trends in psychology. The third chapter analyses and evaluates the reductionistic trends in psychology represented by structuralism, functionalism and behaviourism that resulted in the separation Of psychology from philosophy, instead of being complementary.